HUBUNGAN TUTUP KONTAINER, BAHAN KONTAINER, DAN SUMBER AIR DENGAN TINGKAT KEJADIAN DBD DI WILAYAH KERJA PUSKESMAS NOGOSARI KABUPATEN BOYOLALI - Choirun Nisa; Lintang Dian Saraswati; Martini Martini; Mateus Sakundarno Adi (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2021)
The vectors that cause dengue fever usually live in habitats close to humans, one of which is a water reservoir (TPA) or commonly called a container. In Glonggong Village, containers and water sources are still a problem that triggers the density of larvae. This study aims to determine the relationship between container lids, container materials, and water sources on the incidence of DHF. The total sample used is 110 houses with a total of 201 containers. Collecting data using visual larval techniques, namely only by observing containers that are positive for larvae. Based on the results of the relationship test, it was found that the proportion of the presence of the lid was p = 0.071, container material was p = 0.163, and water source was p = 0.590. Which means that there is a relationship between container lids, container materials, and water sources with the incidence of DHF. Thus, there is a need for further socialization regarding the 3M Plus program in order to suppress dengue cases in Glonggong Village.